Workaholism as Positive Reinforcement for Educators Working Engagement in Higher Education - Destyanto, Twin Yoshua R.; Halim, Lenny (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2024)
Work engagement is an essential indicator for educators to be immersed in their work tasks and to ensure well-being at work. The various tasks and limited time given to educators, especially in higher education, can reduce work engagement. On the other hand, service industry organizations are experiencing a new behavioral phenomenon known as workaholism. This is characterized by employees’ habit of working excessively and compulsively. However, to our knowledge, no study has yet analyzed how workaholism in higher education correlates with educators’ working engagement. Therefore, this study aims to understand the effect and correlation between workaholism level and working engagement in higher education. The 41 lecturers from the Faculty of Industrial Technology at Universitas Atma Jaya Yogyakarta were asked to complete a questionnaire measuring workaholism level (DUWAS) and working engagement (UWES-9). The Pearson analysis of these two variables shows a moderate positive correlation (r = 0.565, p < .001). Moreover, the ANOVA analysis shows lecturers with workaholic behavior have significantly greater engagement levels (p < .05) than those without. This implies that a working environment should be created to promote healthy workaholism among higher education educators to maximize their engagement levels in their work.